Pantoea ananatis, a plant growth stimulating bacterium, and its metabolites isolated from Hydrocotyle umbellata (dollarweed) - Kumudini M. Meepagala; Caleb M. Anderson; Natascha Techen; Stephen O. Duke (Plant Signaling & Behavior)
A bacterium growing on infected leaves of Hydrocotyle umbellata, commonly known as dollarweed, was isolated and identified as Pantoea ananatis. An ethyl acetate extract of tryptic soy broth (TSB) liquid culture filtrate of the bacterium was subjected to silica gel chromatography to isolate bioactive molecules. Indole was isolated as the major compound that gave a distinct, foul odor to the extract, together with phenethyl alcohol, phenol, tryptophol, N-acyl-homoserine lactone, 3-(methylthio)-1-propanol, cyclo(L-pro-L-tyr), and cyclo(dehydroAla-L-Leu). This is the first report of the isolation of cyclo(dehydroAla-L-Leu) from a Pantoea species. Even though tryptophol is an intermediate in the indoleacetic acid (IAA) pathway, we were unable to detect or isolate IAA. We investigated the effect of P. ananatis inoculum on the growth of plants. Treatment of Lemna paucicostata Hegelm plants with 4 × 109 colony forming units of P. ananatis stimulated their growth by ca. five-fold after 13 days. After 13 days of treatment, some control plants were browning, but treated plants were greener and no plants were browning. The growth of both Cucumis sativus (cucumber) and Sorghum bicolor (sorghum) plants was increased by ca. 20 to 40%, depending on the growth parameter and species, when the rhizosphere was treated with the bacterium after germination at the same concentration. Plant growth promotion by Pantoea ananatis could be due to the provision of the IAA precursor indole.